The impact of self-leadership on psychological capital and its influence on fitness instructors' performance - Manz, Bruno Marques Carmo (2022)
With an increased interest in fitness and overall physical health, gyms and fitness academies search for possible ways to stand out in face of competition. Despite that, very few have opted to focus on organizational behaviours. From this, our study focused on the presence of PsyCap in fitness instructors and how (1) self-leadership, when present, may or not be linked to PsyCap, and (2) if PsyCap may or may not impact their performance. A questionnaire survey (n = 42), distributed to fitness instructors that currently living in Portugal, to measure PsyCap was used and cross examined with data previously gathered regarding their self-leadership and performance. From the subsequent analysis, the relationship between self-leadership and PsyCap was indeed positive, while the impact of PsyCap on performance was not proven. The practical implications of this study, self-leadership can be an important factor when evaluating fitness instructors, especially if PsyCap is the target, also when trying to distinguish from the competition, gyms should invest in retaining human capital of interest as it can be a differentiative ingredient when it comes to success.